2018
DOI: 10.1038/s41598-017-18665-4
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombin@Fe3O4 nanoparticles for use as a hemostatic agent in internal bleeding

Abstract: Bleeding remains one of the main causes of premature mortality at present, with internal bleeding being the most dangerous case. In this paper, magnetic hemostatic nanoparticles are shown for the first time to assist in minimally invasive treatment of internal bleeding, implying the introduction directly into the circulatory system followed by localization in the bleeding zone due to the application of an external magnetic field. Nanoparticles were produced by entrapping human thrombin (THR) into a sol-gel der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The best possible solution for such applications is provided by magnetic nanoparticles (MNPs). Their utilizations span various fields such as emergency medical procedures, MRI contrast agent, residue pesticide detection for safe food consumption and separation and purification processes . They also show the capability to act as support for various antibodies or enzymes ,.…”
Section: Methodsmentioning
confidence: 99%
“…The best possible solution for such applications is provided by magnetic nanoparticles (MNPs). Their utilizations span various fields such as emergency medical procedures, MRI contrast agent, residue pesticide detection for safe food consumption and separation and purification processes . They also show the capability to act as support for various antibodies or enzymes ,.…”
Section: Methodsmentioning
confidence: 99%
“…There was carboxyl on SA and phenolic hydroxyl on DA, which would form hydrogen between water molecules in the blood. What's more, Emiliya M et al [ 69 ] reported that hydrogen and electrostatic bonds take part in the formation of the fibrin aggregate. Moreover, the formation of the fibrin aggregate could be accelerant by substance carrying a positive charge.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe 3 O 4 nanoparticles were synthesized by a coprecipitation method, as previously described [26,27]. An amount of 2.5 g FeCl 2 •4H 2 O and 5 g of FeCl 3 •6H 2 O were dissolved with 100 mL of deionized water.…”
Section: Synthesis Of Magnetite Nanoparticles (Mnps)mentioning
confidence: 99%